EFFECTIVENESS OF STARFRUIT LEAF EXTRACT AS A NATURAL ANTIBACTERIAL AGENT IN NATIVE CHICKENS - Devi Y.J.A Moenek; Novianti N. Toelle; Jois M. Jacob; Julita D. Mertha Yasa; I Gusti Komang Oka Wirawan (Buletin Veteriner Udayana, 2025)
Bacterial infections such as Escherichia coli, Staphylococcus aureus, and Salmonella pullorum remain major constraints in native chicken production, reducing productivity and increasing mortality. Excessive use of synthetic antibiotics causes bacterial resistance and residues, thus encouraging the search for safe natural alternatives. This study aimed to evaluate the antibacterial effectiveness of Averrhoa bilimbi L. (bilimbi) leaf extract against bacterial isolates from native chickens and to compare its efficacy with oxytetracycline. The leaves were extracted with 96% ethanol and tested at concentrations of 10%, 20%, and 30% using the disk diffusion method against E. coli isolates. Data were analyzed using the Kruskal-Wallis and Mann–Whitney tests. Results indicated no significant difference (p>0.05) between the inhibition zones of bilimbi leaf extract and oxytetracycline at all concentrations, although descriptively the inhibition zone increased with concentration (average 0.86–1.74 mm). This suggests a concentration-dependent antibacterial activity that remains moderate compared to conventional antibiotics. Bioactive compounds such as flavonoids, tannins, and saponins are presumed to contribute to bacterial growth inhibition. In conclusion, A. bilimbi leaf extract exhibits moderate antibacterial activity. It holds potential as a natural phytobiotic alternative to reduce antibiotic dependence in native chicken production, supporting sustainable and eco-friendly poultry farming. For further research, it is recommended to use: concentration >40% or thick extract from fractionation, further testing of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC).